The Role of Islamic Religious Education in Building Harmony Living With Neighbors in a Multicultural Environment - Jefpi Milda; Karoma; Abdullah Idi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The education of Islamic religion has a strategic role in building social harmony, especially in a multicultural environment. This research aims to explore the contribution of Islamic religious education in forming harmonious neighborly relationships and identify challenges in its implementation. The method used is qualitative research based on literature studies (library research), with analysis of various theoretical and empirical references. The results of the study show that Islamic religious education can be an effective means of instilling the values of tolerance, mutual respect, and building social awareness in a pluralistic society.